Diabetic Wound Healing: Factors, Mechanisms, and Treatment Strategies Using Herbal Components - Porwal, Sejal; Malviya, Rishabha; Sundram, Sonali; Sridhar, Sathvik Belagodu; Shareef, Javedh (Current Drug Targets, 2025)
Managing diabetic wounds is a significant challenge for healthcare professionals since severe complications and delayed recovery greatly impact the patients' quality of life. This article aimed to explore various factors affecting diabetic wound healing, the mechanism of wound healing, and potential natural products having wound healing capability. It focuses on mechanisms of action and the therapeutic effectiveness of the compounds employed in the management of diabetic wounds. The review discusses the function of nutrition in wound healing, emphasizing the significance of consuming adequate amounts of protein, energy, lipids, amino acids, vitamins, minerals, and water to promote healing. Several herbs, including Rosmarinus officinalis, Carica papaya, Aloe vera, Annona squamosa, and Punica granatum, are being tested for wound healing qualities in diabetes circumstances. These plants have a variety of modes of action, including antioxidant, anti-inflammatory, antibacterial, and immunomodulatory activities that help to speed up wound healing, stimulate collagen formation, and promote tissue regeneration. The variety of action mechanisms seen in natural products, especially in plants, offers hope for the treatment of diabetic wounds. It may also be possible to improve healing results and the quality of life of diabetes individuals with chronic wounds by including these herbal treatments in wound care programs.
Keywords: natural products